2016
DOI: 10.18632/oncotarget.7099
|View full text |Cite
|
Sign up to set email alerts
|

Dual mTORC1/2 inhibition induces anti-proliferative effect in NF1-associated plexiform neurofibroma and malignant peripheral nerve sheath tumor cells

Abstract: Approximately 30-50% of individuals with Neurofibromatosis type 1 develop benign peripheral nerve sheath tumors, called plexiform neurofibromas (PNFs). PNFs can undergo malignant transformation to highly metastatic malignant peripheral nerve sheath tumors (MPNSTs) in 5-10% of NF1 patients, with poor prognosis. No effective systemic therapy is currently available for unresectable tumors. In tumors, the NF1 gene deficiency leads to Ras hyperactivation causing the subsequent activation of the AKT/mTOR and Raf/MEK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
40
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 49 publications
5
40
0
1
Order By: Relevance
“…Given their critical role in regulating the AKT-mTOR pathway, the loss of function of NF1 and TSC1/TSC2 identified in our study provides a rationale for investigating mTOR complex (mTORC) inhibitors in both MPNSTs and SDMs [22]. Preclinical studies have suggested a synergistic antiproliferative effect of combined mTORC1/2 and MEK pathway inhibitors or bromo-domain-containing protein 4 inhibitors in cell lines with NF1 deficiency [19]. This…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Given their critical role in regulating the AKT-mTOR pathway, the loss of function of NF1 and TSC1/TSC2 identified in our study provides a rationale for investigating mTOR complex (mTORC) inhibitors in both MPNSTs and SDMs [22]. Preclinical studies have suggested a synergistic antiproliferative effect of combined mTORC1/2 and MEK pathway inhibitors or bromo-domain-containing protein 4 inhibitors in cell lines with NF1 deficiency [19]. This…”
Section: Discussionmentioning
confidence: 61%
“…Our findings corroborate those results by showing deleterious NF1 mutations in the majority of MPNSTs and SDMs analysed. Loss of NF1 can lead to RAS activation and promote signalling along at least two main pathways, the AKT–mammalian target of rapamycin (mTOR) pathway and the mitogen‐activated protein kinase (MAPK) pathway . In our series, NF1 deleterious mutations and/or deep/homozygous deletions were identified in 70% of both SDMs and MPNSTs, with half (35%) of these mutations involving the RAS‐binding domain.…”
Section: Discussionmentioning
confidence: 85%
“…Drugs that can inhibit the dysregulation induced by neurofibromin deficiency are potential targets, such as rapamycin, an mTOR inhibitor that has been shown to attenuate PH and neo-intimal formation in rats [62]. A recent study also showed that a stronger inhibition of mTOR by a dual mTORC1/2 inhibitor induced an anti-proliferative effect in NF1-associated plexiform neurofibroma and malignant peripheral nerve sheath tumour cells compared to rapamycin which is only an inhibitor of mTORC1 [63]. Attenuation of the vascular wall proliferation that characterises NF1 using statins (3-hydroxy-3-methylglutarylcoenzyme A reductase inhibitors) is another possible approach, since this class of agent is known to inhibit Ras activity through prevention of its lipid modification [64].…”
Section: Treatment Of Ph Associated With Nf1mentioning
confidence: 99%
“…NF1-related MPNSTs have been shown to arise from NF1-null myelinating Schwann cells where neurofibromin deficiency results in RAS deregulation (10)(11)(12)(13)(14)(15). Plexiform neurofibromas are the benign precursor of NF1-related MPNSTs and are formed by a recruited admixture of NF1 haploinsufficient cells (fibroblasts, mast cells, and perineurial cells) following an initial NF1-loss-of-heterozygosity event in a peripheral nerve Schwann cell (16)(17)(18). A variety of genomic alterations have been observed in the malignant transformation of benign plexiform neurofibromas into MPNSTs including deleterious mutations that impact cell cycle regulation (CDKN2A), apoptosis (TP53), tumor suppression (PTEN, RASSF1A) and chromatin modification (SUZ12/PRC2 gene family) (19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%